2019
DOI: 10.1093/jac/dkz241
|View full text |Cite
|
Sign up to set email alerts
|

ISAba1-dependent overexpression of eptA in clinical strains of Acinetobacter baumannii resistant to colistin

Abstract: Background Colistin resistance in Acinetobacter baumannii often results from mutational activation of the two-component system PmrAB and subsequent addition of phospho-ethanolamine (pEtN) to lipooligosaccharide by up-regulated pEtN transferase PmrC. Objectives To characterize mechanisms of colistin resistance independent of PmrCAB in A. baumannii. Methods Twe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 28 publications
4
14
0
Order By: Relevance
“…eptA is a pmrC homologue with pEtN transferase activity [8]. In this study, eptA was present in both CR-ColSAB and CR-ColRAB and comparable with previous studies [3, 7 -8, 35].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…eptA is a pmrC homologue with pEtN transferase activity [8]. In this study, eptA was present in both CR-ColSAB and CR-ColRAB and comparable with previous studies [3, 7 -8, 35].…”
Section: Discussionsupporting
confidence: 91%
“…baumannii [32]. Earlier studies reported IC2/global clone 2 (GC2) as the predominant lineage associated with outbreaks [8]. This finding correlates with the current study and identified in both CR-ColRAB and CR-ColSAB In the present study, IC1/GC1was identified among CR-ColSAB which is contrast to Snyman et al where GC1 was identified in both CR-ColSAB and CR-ColRAB [33].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Colistin resistance may also result from the overexpression of etpA, a pmrC homolog. This is mediated by insertional inactivation of a gene encoding an H-NS family transcriptional regulator (Lucas et al, 2018) or by integration of insertion sequence elements upstream of the eptA gene itself (Gerson et al, 2019;Potron et al, 2019;Trebosc et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…pmrA, phoPQ, mgrB, and lpxACD reported in other Gramnegative bacteria were not found in this study. 23,46,51,52 The above results indicate that PmrB-sd mutations contributed to, but were not fully responsible for, HLCR in APEC strains. Two possible mechanisms might be contributed to HLCR in E. coli: (1) pmrB mutation coupled with mutation in genes involved in LPS modification and hyperproduction of capsular polysaccharide, or encoding porins and efflux pumps 23,[53][54][55] ;…”
Section: High-level Colistin Resistance In Apecmentioning
confidence: 86%